AKIBAT HUKUM DALAM PERJANJIAN JUAL BELI BARANG YANG AKAN ADA - Rafa Azri Julian Humaer (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The purpose of this study is to know clearly the implementation of the sale and purchase agreement of goods (tobacco) which will exist in terms of the Civil Code and the legal consequences arising from the sale and purchase of goods (tobacco) which will exist in terms of the Civil Code. The research method used is normative and empirical research. Based on the results of the research note that the sale of new goods (tobacco) aka tone in the future is legitimate because in accordance with the terms of the validity of the agreement set forth in the Civil Code and which bear the risk of disappearance of the object of the agreement is dependent of how the object is destroyed.